Modified bacterial cellulose stabilized ASA sizing agent emulsion as well as preparation method and application thereof

By using Pickering emulsion technology that combines modified bacterial cellulose with nanosilver and nanosilica particles in ASA emulsion, the stability and storage problems of ASA emulsion are solved, and efficient paper glue application effect is achieved, enhancing the multifunctional performance of the paper.

CN119640616AActive Publication Date: 2025-03-18QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510077259.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing ASA emulsion emulsification system has stability and storage problems, and it is difficult to maintain good performance under long-term storage conditions, and the limitations of relying on surfactants are significant.

Method used

ASA Pickering emulsion preparation method based on modified bacterial cellulose was adopted, and TBC@Ag@SiO2 particles were formed by combining TEMPO oxidized bacterial cellulose nanofibers with nanosilver and nanosilica particles, which was used as a stabilizer for the emulsion, and additional surfactant was avoided.

Benefits of technology

It significantly improves the interface stability and long-term storage stability of ASA emulsion, reduces the amount of emulsification stabilizer, improves the water resistance, antibacteriality and ultraviolet resistance of paper, and provides innovative solutions for green and environmentally friendly paper glue application technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640616A_ABST
    Figure CN119640616A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of papermaking, and provides a modified bacterial cellulose stabilized ASA sizing agent emulsion. The TEMPO oxidized bacterial cellulose nanofiber suspension and the silver ammonia solution are heated to react, and TBC-coated Ag is obtained; dropwise adding TEOS (tetraethyl orthosilicate) into the ethanol dispersion liquid of the TBC (at) Ag, stirring and reacting to obtain TBC (at) Ag (at) SiO2; aSA is added into the TBC (at) Ag (at) SiO2 aqueous dispersion to be sheared and emulsified, and the modified bacterial cellulose stabilized ASA sizing agent emulsion can be obtained. The prepared ASA emulsion can effectively block the influence of environmental factors on the emulsion, the interface stability of the emulsion is remarkably improved, no additional surfactant needs to be added, the sizing process is simpler and more convenient, the long-term stability of the ASA emulsion is effectively improved, a water phase and an oil phase are prevented from being separated, and the water resistance, the antibacterial property and the ultraviolet resistance of paper are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of papermaking sizing agent preparation, and relates to the preparation of an ASA sizing agent emulsion. Background Art

[0002] The disclosure of this background information is intended to enhance understanding of the general background of the invention and should not necessarily be taken as an acknowledgment or any form of suggestion that this information constitutes the prior art already known to a person skilled in the art.

[0004] At present, ASA sizing agents are usually emulsified on site using cationic starch and low molecular weight surfactants and need to be used immediately. However, the use process of cationic starch is relatively complicated. It needs to be gelatinized and cooled before it can be added, which increases the complexity of the emulsification process and is difficult to control accurately. It may also cause sedimentation and blanket clogging problems. At the same time, the surfactants used may have adverse effects on the sizing effect and the environment. In recent years, research on the emulsification preparation of ASA has made significant progress, and related technical achievements have become increasingly abundant, providing new solutions for the application of ASA in the papermaking industry.

[0005] In the study of improving the stability and sizing effect of ASA (alkenyl succinic anhydride) emulsion, inorganic particles and organic emulsifiers are widely used to improve its performance. However, these methods still have obvious limitations in practical applications. For example, Chinese patent CN102268839B discloses a Pickering emulsion type ASA sizing agent using quaternary ammonium salt intercalated nano cationic modified montmorillonite as an emulsifier. By combining with magnesium salt to form an aqueous phase, ASA can be emulsified without a surfactant. However, while the use of inorganic particles brings initial stability, it also limits high-concentration applications due to its low emulsion concentration and poor storage stability, and it is difficult to maintain good performance under long-term storage conditions. Similarly, Chinese patent CN102493272A uses hectorite and nano titanium dioxide as emulsifiers, and forms a stable emulsion through appropriate pH adjustment and mechanical shearing. Although this method reduces the use of surfactants to a certain extent, the emulsion system relying on inorganic particles still cannot avoid the problem of hydrolysis, and the sizing activity of ASA decreases during long-term storage. In terms of organic emulsifiers, Chinese patent CN104746388A improves the sizing effect of ASA by adding papermaking filler particles modified by hydroxyl-containing natural hydrocarbon polymer polysaccharide compounds to the pulp. This method enhances the retention rate of ASA on the fiber surface and reduces the deposition problem caused by hydrolysis. However, this technology still requires a higher amount of emulsifier to maintain stability, which increases production costs and environmental burden. In addition, Chinese patent CN109989293A proposes to use a specific proportion of emulsifiers and a strong shear force emulsification pump in the ASA emulsion to control the emulsion particle size to improve its stability and sizing effect. Although this method enhances the uniformity and durability of the emulsion, the limitations of relying on surfactants are still significant. Summary of the invention

[0006] In order to overcome the problems existing in the existing ASA emulsion emulsification system, the present invention provides a preparation method of an ASA Pickering emulsion stabilized by modified bacterial cellulose and its application in internal sizing. The ASA Pickering emulsion can be stably formed without adding a surfactant to the emulsion.

[0007] Another object of the present invention is to provide a process method suitable for internal sizing of paper pulp for the above-mentioned ASA sizing agent. The prepared sized paper not only has good water resistance, but also has antibacterial function and ultraviolet blocking performance, further expanding its value in special paper.

[0008] To achieve the above purpose, the present invention adopts the following technical solution.

[0009] A method for preparing an ASA sizing agent comprises the following steps: (1) The suspension of TEMPO-oxidized bacterial cellulose nanofibers (TBC) and silver ammonia solution were heated to react, and then centrifuged to wash and remove impurities to obtain oxidized bacterial cellulose loaded with nanosilver particles (TBC@Ag); (2) Add ethyl silicate (TEOS) to the ethanol dispersion of TBC@Ag, stir for reaction, and then centrifuge for washing to remove impurities, thereby obtaining oxidized bacterial cellulose loaded with nano-silver particles and nano-silicon dioxide particles (TBC@Ag@SiO2); (3) Add ASA to the TBC@Ag@SiO2 dispersion and obtain the ASA Pickering sizing emulsion after shearing and emulsification.

[0010] In step (1), the TEMPO-oxidized bacterial cellulose nanofibers can be obtained by a method in the prior art, such as catalytic oxidation of bacterial cellulose nanofibers in an aqueous solution with a pH of about 10 using a TEMPO / NaBr / NaClO system. In order to increase the reaction rate and oxidation degree, ultrasonic treatment can also be assisted during the reaction. Specifically, the steps are: adding NaBr and TEMPO to the bacterial cellulose nanofiber suspension, then adding a NaClO solution, adjusting the pH to 10-10.5 for reaction, and after terminating the reaction, adjusting the system pH to neutral, filtering and washing to remove impurities, and obtaining TEMPO-oxidized bacterial cellulose nanofibers. The addition ratio of the bacterial cellulose nanofibers, NaBr, TEMPO and NaClO is 1 g: 0.1 mmol: 9.72 mmol: (20-60.4) mmol.

[0011] In step (1), the silver ammonia solution is prepared by dissolving 0.1 g of silver nitrate in 20 mL of deionized water to prepare a 0.5 wt% silver nitrate solution, then adding 1 mL of a 20% ammonia solution and stirring thoroughly to form a silver ammonia solution; at this time, the silver ammonia concentration of the solution is 0.396 wt%.

[0012] In step (1), the mass ratio of silver ammonia to TBC is not limited; preferably, the mass ratio of silver ammonia to TBC is 0.069:0.82.

[0013] In step (1), the reaction temperature is 70°C-90°C; and the reaction time is 0.5 h-2 h.

[0014] In step (2), the mass ratio of TBC@Ag to TEOS is 1:4.64-13.95.

[0015] In step (2), the reaction time is 6 h-18 h.

[0016] In the TBC@Ag@SiO2, silica particles with a particle size of 20 nm-40 nm are bonded to the hydroxyl groups of oxidized bacterial cellulose through silicon-oxygen bonds (Si-OC); silver particles with a particle size of 30 nm-90 nm are bonded to the hydroxyl groups of oxidized bacterial cellulose through coordination bonds.

[0017] In step (3), the concentration of the TBC@Ag@SiO2 dispersion is 0.2wt%-1wt%.

[0018] In step (3), the mass ratio of ASA to TBC@Ag@SiO2 is (125-25):1, more preferably 50:1.

[0019] In step (3), the shear emulsification rate is 5000 rpm-20000 rpm; more preferably 10000 rpm-12000 rpm.

[0020] In step (3), the shear emulsification time is 1 min-8 min; more preferably 3 min-4 min.

[0021] In step (3), the concentration of ASA in the ASA Pickering sizing emulsion is 10 wt%-40 wt%.

[0022] An ASA emulsion obtained by the above preparation method; the average particle size of the droplets in the emulsion is 5-10 μm.

[0023] A paper prepared from the ASA emulsion.

[0024] The present invention has the following advantages: The TBC@Ag@SiO2 used in the present invention is a bacterial cellulose-based granular material with antibacterial and anti-ultraviolet properties, with nanosilver (Ag) and silicon dioxide (SiO2) loaded on the surface, thereby giving the material broad-spectrum antibacterial and anti-ultraviolet capabilities. As a stabilizer for Pickering emulsions, TBC@Ag@SiO2 can form a dense and stable fiber film at both the ASA-water and oil-water interfaces, effectively blocking the influence of environmental factors on the emulsion, and significantly improving the interfacial stability of the emulsion. In the sizing of ASA emulsions, TBC@Ag@SiO2 not only reduces the amount of emulsifier stabilizer, but also avoids the addition of additional surfactants, making the sizing process simpler, effectively improving the long-term stability of ASA emulsions, preventing the separation of water and oil phases, and improving the water resistance, antibacterial and anti-ultraviolet properties of paper, providing an innovative solution for green and environmentally friendly paper sizing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1is the infrared spectra of TBC@Ag@SiO2, TBC and bacterial cellulose nanofibers (BC); Figure 2 This is the scanning electron microscope image of TBC@Ag@SiO2; Figure 3 This is a microscopic picture of the ASA sizing agent emulsion with TBC@Ag@SiO2 as stabilizer; Figure 4 The comparison of the liquid-repellent effect of ASA sizing emulsion stabilized by TBC@Ag@SiO2 on paper sized in pulp and unsized paper; Figure 5 is the dynamic three-phase contact angle between BC and TBC@Ag@SiO2; Figure 6 It is a comparison of the weight loss of unsized paper and sized paper during the process of preserving strawberries. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with the examples and drawings, but the present invention is not limited by the following examples. Unless otherwise specified, the sizing method, sizing degree measurement, contact angle measurement and paper UV transmittance measurement methods in each example are as follows: (1) Gluing method Before sizing, the ASA sizing emulsion was diluted to 0.2%, the pulp concentration was adjusted to 1%, and 1% aluminum sulfate (relative to the mass percentage of absolute dry pulp) was added to the pulp at a stirring rate of 500 rpm. Then, the slurry pH was adjusted to 7.5-8.5 with 1 mol / L sodium hydroxide solution, and then ASA emulsion and 0.03% CPAM were added in sequence. Then, the mixture was stirred at 500 rpm for 2 min and allowed to stand for 30 s. Then, a PTI paper sheet maker (RK3AKWT, Austria) was used to make hand sheets. The basis weight of the hand sheets was 60 g / m 2 (T205 om-88, TAPPI), the papermaking system is in accordance with ISO5289 / 2 and DIN54358 standards, and the Kaiser method manual papermaking mode is selected for papermaking. The papermaking hand sheet is dried at 105℃, and then the paper moisture is balanced at room temperature for 24 hours, and the ambient humidity is 50%.

[0027] (2) Determination of sizing degree The sizing performance is evaluated by measuring the sizing degree of papermaking paper (GB / T5405-2002). Before the measurement, the paper was cut into 30×30 mm square pieces and placed in a 25°C, 50% humidity environment to balance the moisture for 24 h. The four sides of the paper were folded to form a boat-shaped structure with a bottom area of ​​about 20×20 mm, and then floated in a 2% dilute ammonium thiocyanate solution. A drop of 0.5 μL of 1% ferric chloride solution was dropped on the upper part of the boat-shaped paper with a rubber-tipped dropper. At the same time, a stopwatch was used to time the time. When a red spot appeared in the middle of the ferric chloride droplet, the timing ended, and the time was the sizing degree of the paper sample. The front and back sides of the test sample were measured 10 times each, and the average value was taken.

[0028] (3) Contact angle measurement The contact angle of paper was measured using a fully automatic video optical contact angle meter. First, ensure that the sample surface is clean and flat, and fix the paper sample horizontally on the measuring platform. Use a drop volume of 5 μL and deionized water as the test liquid. Use an automatic injection system to accurately add a constant volume of droplets on the surface of the paper, start the measurement program to automatically collect the side view image of the droplet, and the system automatically identifies the droplet contour and calculates the contact angle. To ensure the accuracy and representativeness of the measurement results, select 10 different measurement positions on the front and back of the paper, record the contact angle data, and take the average value of the front and back measurements.

[0029] (4) Paper UV transmittance Place the paper sample on a fixture to ensure that the light passes through the sample vertically; scan with a UV-visible spectrophotometer at a UV wavelength of 200-400 nm to measure the sample transmittance.

[0030] Example 1 Preparation of ASA emulsion (1) NaBr and TEMPO were added to a 1 wt% bacterial cellulose nanofiber suspension to dissolve it, and then NaClO solution was added to make the ratio of bacterial cellulose nanofiber, NaBr, TEMPO and NaClO be 1 g:0.1 mmol:9.72 mmol:20 mmol; the pH was adjusted to 10-10.5 and stirred for 1 h. After terminating the reaction by adding 10 mL of anhydrous ethanol, the pH of the system was adjusted to about 7, and the precipitate was obtained by filtration. The precipitate was washed several times to remove impurities, and TEMPO-oxidized bacterial cellulose nanofiber (TBC) was obtained; (2) Dissolve 0.1 g of silver nitrate in 20 mL of deionized water to prepare a 0.5 wt% silver nitrate solution; add 1 mL of 20% ammonia solution and stir thoroughly to form a silver ammonia solution with a concentration of 0.396 wt%; Add all of the above 21 mL of silver-ammonia solution into 100 mL of 1% TBC suspension to obtain a mixed solution in which the concentration of silver-ammonia is 0.069 wt% and the concentration of TBC is 0.82 wt%; The mixed solution was reacted in a water bath at 80°C for 1 h to obtain TBC loaded with silver particles (TBC@Ag); (3) Disperse 100 mL of 1% TBC@Ag solution in 300 mL of anhydrous ethanol, then add TEOS to make the mass ratio of TBC@Ag to TEOS 1:5, react for 12 h, centrifuge to obtain a precipitate, and centrifuge and wash multiple times to obtain oxidized bacterial cellulose loaded with nanosilver particles and nanosilicon dioxide particles (TBC@Ag@SiO2); its infrared spectrum is shown in Figure 1 Shown: Bacterial cellulose (BC) at 3400-3500 cm -1 The hydroxyl stretching vibration peak at 2900 cm -1 The CH stretching vibration peak at 1100-1200 cm -1 The COC stretching vibration peaks reveal the presence of methyl, methylene groups and glycosidic bonds in the cellulose molecules. After conversion to TEMPO-oxidized bacterial cellulose (TBC), the hydroxyl peak weakened, while at 1720-1750cm -1 The carboxyl stretching vibration peak appeared at 1100 cm-1, indicating that TEMPO oxidation successfully converted part of the hydroxyl groups into carboxyl groups. Furthermore, when nanosilver and nanosilicon dioxide were attached to the surface of oxidized bacterial cellulose to form TBC@Ag@SiO2, the hydroxyl peak was further weakened, and the Si-O-Si stretching vibration peak was at 1100 cm-1. -1 Appears near and is between 500-600 cm -1 Ag-O or Si-OC related vibration peaks appeared at , confirming the successful attachment of nanosilver and nanosilicon dioxide; In the above steps, the surface of bacterial cellulose (TBC) after TEMPO oxidation treatment is negatively charged and can react with silver ammonium ions ([Ag(NH3)2] + ) undergoes ion exchange to replace the sodium ions. In this process, on the one hand, silver ammonium ions are stably attached to the TBC surface through electrostatic interactions; on the other hand, silver ammonium ions are tightly attached to the cellulose surface and can also promote the reduction of silver ions to metallic silver (Ag), thereby forming silver nanoparticles (AgNPs).

[0031] Scanning electron microscopy Figure 2 As shown: bacterial cellulose is about 20 μm long and 50-100 nm in diameter, nanosilver particles are 30-90 nm in diameter, and nanosilicon dioxide particles are 20-40 nm in diameter; (4) 0.2 parts by weight of TBC@Ag@SiO2 was dispersed in 100 parts of water, 25 parts by weight of ASA was added, and shear emulsification was performed at 8000 rpm for 2 min to prepare an ASA sizing emulsion with an internal phase volume fraction of 20%. The obtained ASA sizing agent had a uniform appearance, and the emulsion micrograph ( Figure 3 ) showed that the average droplet size was 8.6 μm, and there was no phase separation or demulsification after 72 hours, indicating that the emulsion had excellent stability.

[0032] After the newly prepared ASA emulsion was left for 1 hour, it was diluted to 0.1% with deionized water and used for internal sizing of pulp. The ASA dosage was 0.5%. The sizing degree of the obtained sized paper was 623 seconds, and the UV transmittance of the paper at 365 nm was only 16.38%. Figure 4 and Figure 5 The comparison of the lyophobic effect and dynamic three-phase contact angle of base paper and sized paper respectively shows that the paper after sizing with ASA emulsion shows excellent waterproof performance. The water contact angle of sizing paper reaches 121°. After the ASA emulsion is placed for 72 hours, the emulsion volume fraction of the sizing agent does not change. The above sizing steps are repeated, and the sizing degree of the sizing paper obtained is 534 seconds, which is enough to ensure the sizing quality during transportation and use, and the ultraviolet transmittance of the paper shows excellent optical shielding effect. Even after being placed for 30 days, the emulsion volume fraction of the ASA emulsion can still reach 99%, and the sizing degree still reaches 397 seconds, maintaining good sizing performance, proving that this ASA sizing emulsion has excellent storage stability.

[0033] Example 2 Preparation of TBC@Ag@SiO2 and AKD emulsion 1. Preparation of TBC@Ag@SiO2 (1) NaBr and TEMPO were added to a 1 wt% bacterial cellulose nanofiber suspension to dissolve it, and then a 10% NaClO solution was added to make the ratio of bacterial cellulose nanofiber, NaBr, TEMPO and NaClO be 1 g:0.1 mmol:9.72mmol:40 mmol; the pH was adjusted to 10-10.5 and stirred for 1 h. After terminating the reaction by adding 10 mL of anhydrous ethanol, the pH of the system was adjusted to about 7, and the precipitate was obtained by filtration. The precipitate was washed several times to remove impurities, and TEMPO-oxidized bacterial cellulose nanofiber (TBC) was obtained; (2) Dissolve 0.1 g of silver nitrate in 20 mL of deionized water to prepare a 0.5 wt% silver nitrate solution; add 1 mL of 20% ammonia solution and stir thoroughly to form a silver ammonia solution with a concentration of 0.396 wt%; Add all of the above 21 mL of silver-ammonia solution into 100 mL of 1% TBC suspension to obtain a mixed solution in which the concentration of silver-ammonia is 0.069 wt% and the concentration of TBC is 0.82 wt%; The mixed solution was reacted in a water bath at 80°C for 1 h to obtain TBC loaded with silver particles (TBC@Ag); (3) Disperse 100 mL of 1% TBC@Ag solution in 300 mL of anhydrous ethanol, then add TEOS to make the mass ratio of TBC@Ag to TEOS 1:10, react for 12 h, centrifuge to obtain a precipitate, and centrifuge and wash multiple times to obtain oxidized bacterial cellulose loaded with nanosilver particles and nanosilicon dioxide particles (TBC@Ag@SiO2); (4) 0.5 parts by weight of TBC@Ag@SiO2 was dispersed in 100 parts by weight of water, 50 parts by weight of ASA was added, and shear emulsification was performed at a rotation speed of 10,000 rpm for 3 min to prepare an ASA sizing emulsion with an internal phase volume fraction of 33%.

[0034] The average droplet size of the emulsion is 5.2 μm. After 72 hours of placement, there is no phase precipitation and demulsification, indicating that the emulsion has good stability. The newly prepared ASA sizing emulsion (placed for 1 hour) was diluted to 0.2% with deionized water for paper pulp sizing. The ASA dosage was 0.5%, and the sizing degree of the obtained sized paper was 977 s. After the ASA sizing emulsion was placed for 72 hours, the above steps were repeated. The sizing degree of the obtained sized paper was 793 s, which was sufficient to ensure the sizing quality during transportation and use. The transmittance of the paper at 365 nm was only 7.47%. The water contact angle of the sized paper reached 118°. Even after 30 days of placement, the emulsion volume fraction of the sizing agent was still 100%; after repeating the above steps, the sizing degree of the obtained sized paper still reached 522 s, and the sizing performance was still good, indicating that the prepared ASA sizing emulsion has excellent storage stability.

[0035] Example 3 Preparation of TBC@Ag@SiO2 and AKD emulsion 1. Preparation of TBC@Ag@SiO2 (1) NaBr and TEMPO were added to a 1 wt% bacterial cellulose nanofiber suspension to dissolve it, and then a 10% NaClO solution was added to make the ratio of bacterial cellulose nanofiber, NaBr, TEMPO and NaClO be 1 g:0.1 mmol:9.72mmol:60.4 mmol; the pH was adjusted to 10-10.5 and stirred for 1 h. After terminating the reaction by adding 10 mL of anhydrous ethanol, the pH of the system was adjusted to about 7, and the precipitate was obtained by filtration. The precipitate was washed several times to remove impurities, and TEMPO-oxidized bacterial cellulose nanofiber (TBC) was obtained; (2) Dissolve 0.1 g of silver nitrate in 20 mL of deionized water to prepare a 0.5 wt% silver nitrate solution; add 1 mL of 20% ammonia solution and stir thoroughly to form a silver ammonia solution with a concentration of 0.396 wt%; Add all of the above 21 mL of silver-ammonia solution into 100 mL of 1% TBC suspension to obtain a mixed solution in which the concentration of silver-ammonia is 0.069 wt% and the concentration of TBC is 0.82 wt%; The mixed solution was reacted in a water bath at 80°C for 1 h to obtain TBC loaded with silver particles (TBC@Ag); (3) Disperse 100 mL of 1% TBC@Ag solution in 300 mL of anhydrous ethanol, then add TEOS to make the mass ratio of TBC@Ag to TEOS 1:10, react for 12 h, centrifuge to obtain a precipitate, and centrifuge and wash multiple times to obtain oxidized bacterial cellulose loaded with nanosilver particles and nanosilicon dioxide particles (TBC@Ag@SiO2); (4) 1 part by weight of TBC@Ag@SiO2 was dispersed in 100 parts by weight of water, and 100 parts by weight of ASA was added. The mixture was sheared and emulsified at a speed of 15,000 rpm for 4 min to prepare an ASA sizing emulsion with an internal phase volume fraction of 50%. The average particle size of the emulsion droplets was 6.5 μm. After being left for 72 hours, there was no phase precipitation and no demulsification phenomenon, and the emulsion had good stability.

[0036] The prepared ASA sizing emulsion (standing time of 1h) was diluted to 0.2% with deionized water for paper pulp sizing. The sizing degree of the sized paper obtained with an ASA dosage of 0.5% was 782 s; the prepared ASA sizing emulsion was placed for 72h and the above steps were repeated. The sizing degree of the sized paper obtained was 584 s, which was enough to ensure the sizing quality during transportation and use. The transmittance of the paper at 365nm was only 3.86%. The water contact angle of the sized paper reached 127°. After the prepared ASA emulsion was placed for 30 days, the emulsion volume fraction still reached 99%; the sizing degree of the sized paper obtained by repeating the above steps was 467s, and the sizing performance was still maintained, indicating that the prepared ASA sizing emulsion has good storage stability.

[0037] Comparative Example 1 Preparation of BC-stabilized ASA emulsion 0.2 parts by weight of bacterial cellulose nanofibers were dispersed in 100 parts of water, 25 parts by weight of ASA were added, and shear emulsification was performed at a rotation speed of 10000 rpm for 2 min to prepare an ASA sizing emulsion with an internal phase volume fraction of 20% and an average particle size of emulsion droplets of 14.7 μm.

[0038] Application Example 1 Preparation of sized paper Before sizing, the ASA sizing emulsion obtained in Example 1 and Comparative Example 1 was diluted to 0.2%, the pulp concentration was adjusted to 1%, and 1% aluminum sulfate (relative to the mass percentage of absolute dry pulp) was first added to the pulp at a stirring rate of 500 rpm. Then, the slurry pH was adjusted to 7.5-8.5 with a 1 mol / L sodium hydroxide solution, and then ASA emulsion and 0.03% CPAM were added in sequence. Then, the mixture was stirred at a speed of 500 rpm for 2 min and then allowed to stand for 30 s. Then, a PTI paper sheet making machine (RK3AKWT, Austria) was used to make a hand sheet, and the basis weight of the hand sheet was 60 g / m 2 (T205 om-88, TAPPI), the papermaking system was in accordance with ISO5289 / 2 and DIN54358 standards, and the Kaiser manual papermaking mode was selected for papermaking. The hand-made sheets were dried at 105°C, and then the paper moisture was balanced at room temperature for 24 h, and the ambient humidity was 50%, and BC ASA sizing paper (Comparative Example 1) and TBC@Ag@SiO2ASA sizing paper (Example 1) were obtained respectively.

[0039] Application Example 2: Freshness-preserving effect of paper after sizing The strawberries were placed in a transparent glass fresh-keeping box, and the top of the fresh-keeping box was sealed with different sizing papers prepared in Application Example 1, and the unsizing paper was used as a control. Then it was stored at room temperature and observed for 9 days. During the observation period, the strawberries were weighed regularly using a digital balance to obtain and quantify the water loss data of the strawberries; at the same time, the changes in the color and morphology of the strawberry fruits were recorded by taking photos regularly.

[0040] Weight loss rate = , Among them, m1 is the initial weight and m2 is the weight during the test on a certain day.

[0041] The control sample had the highest weight loss, reaching nearly 6% by the seventh day. In contrast, strawberry wrappers treated with ASA emulsion prepared with TBC@Ag@SiO2 showed minimal weight loss during storage, remaining below 2%, significantly outperforming the ASA emulsion-treated wrappers prepared with BC.

[0042] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.

Claims

1. A method for preparing an ASA sizing agent, characterized in that: The following steps are involved: (1) The TEMPO-oxidized bacterial cellulose nanofiber suspension and the silver ammonia solution were heated to react, and then centrifuged to wash and remove impurities to obtain TBC@Ag; (2) Add ethyl silicate to the ethanol dispersion of TBC@Ag, stir for reaction, and then centrifuge for washing to remove impurities to obtain TBC@Ag@SiO2; (3) Add ASA to the TBC@Ag@SiO2 dispersion and obtain the ASA Pickering sizing emulsion after shearing and emulsification.

2. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the TEMPO-oxidized bacterial cellulose nanofibers is as follows: the bacterial cellulose nanofibers are obtained by catalytic oxidation using a TEMPO / NaBr / NaClO system in an aqueous solution with a pH of about 10.

3. The preparation method according to claim 2, characterized in that: Ultrasonic treatment was used during the reaction.

4. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the TEMPO-oxidized bacterial cellulose nanofibers is as follows: NaBr and TEMPO are added to the bacterial cellulose nanofiber suspension, and then a NaClO solution is added, and the pH is adjusted to 10-10.5 for reaction. After the reaction is terminated, the pH of the system is adjusted to neutral, and the suspension is filtered and washed to remove impurities, thereby obtaining TEMPO-oxidized bacterial cellulose nanofibers. The addition ratio of the bacterial cellulose nanofibers, NaBr, TEMPO and NaClO is 1 g: 0.1 mmol: 9.72 mmol: (20-60.4) mmol.

5. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of silver ammonia to TEMPO oxidized bacterial cellulose nanofibers is 0.069:0.82; In step (1), the reaction temperature is 70°C-90°C; the reaction time is 0.5 h-2 h; In step (2), the mass ratio of TBC@Ag to ethyl silicate is 1:(4.64-13.95); In step (2), the reaction time is 6 h-18 h; In step (3), the concentration of TBC@Ag@SiO2 dispersion is 0.2wt%-1wt%; In step (3), the mass ratio of ASA to TBC@Ag@SiO2 is (125-25):1; In step (3), the shear emulsification rate is 5000 rpm-20000 rpm;. In step (3), the shear emulsification time is 1 min to 8 min; In step (3), the concentration of ASA in the ASA Pickering sizing emulsion is 10 wt%-40 wt%.

6. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of ASA to TBC@Ag@SiO2 is 50:1; In step (3), the shear emulsification rate is 10000 rpm-12000 rpm; In step (3), the shear emulsification time is 3 min-4 min.

7. The preparation method according to claim 1, characterized in that: In step (1), the silver ammonia solution is prepared by dissolving 0.1 g of silver nitrate in 20 mL of deionized water to prepare a 0.5 wt% silver nitrate solution, then adding 1 mL of 20% ammonia solution and stirring thoroughly to form a silver ammonia solution.

8. An ASA emulsion obtained by the preparation method as described in any one of claims 1 to 7.

9. The ASA emulsion according to claim 8, characterized in that The average particle size of the droplets in the ASA emulsion is 5-10 μm.

10. A paper prepared from the ASA emulsion according to claim 8 or 9.

Citation Information

Patent Citations

  • Method for preparing Pickering emulsion from TEMPO oxidized bacterial cellulose

    CN106040026A

  • Method for preparing Pickering emulsion from millet starch

    CN112759772A

  • Preparation and application of Pickering emulsion with efficient antibacterial property and hydrophobicity

    CN118725655A

  • Paper size mixtures

    US20100016478A1

  • Process for sizing paper and sizing composition

    WO2003044274A1